Protest and video activism. (16th November 2012) - Chanan, Michael
Almost every one of the popular protest movements that have sprung up in the past couple of years in different parts of the world has taken to the Internet in a big way to organize and express itself. Indeed activists have proved extraordinarily adept in the use of the social media. There is a paradox in the way that growing numbers of people are using the products of consumerism to try and combat the power of the same global corporate capitalism that sells them these very tools and instruments of free counter-cultural production to begin with. This paradox has a history that this article brings back to mind, because one of the things about capitalism is that it not only creates the technologies employed in the mass media, but it cannot resist making consumer versions of the same gear – it is a simple question of maximizing the opportunities for consumption and profits – and the consequences are often contradictory.